Case Report: Pott's Edematous Tumor: Complicated Frontal Sinusitis - An Unremembered Diagnosis - Silva, Ana Cristina Veiga; Lins, Camila Mendonça; Mendes, Renan Furtado de Almeida; Silva, Marcelo Henrique Simões; de Alencar Neto, Joaquim Fechine; Lopes, Caio César Maia; Ferraz, Gabriela Lisboa de Souza; de Sousa, Diego Felipe Rodrigues; Bem Junior, Luiz Severo; Valença, Marcelo Moraes; Azevedo-Filho, Hildo Rocha Cirne de (Frontiers in Surgery, 2022)
Pott's Puffy tumor (PPT), also called Pott's Edematous Tumor, is a subperiosteal abscess of the frontal bone, associated with osteomyelitis of the frontal bone. In this paper, we report the case of a 16-year-old patient who presented with headache associated with progressive forehead swelling and fever. Clinical and imaging exams pointed to the hypothesis of Pott's Edematous Tumor associated with brain abscess. Patient was submitted to surgical excision of the abscess and treatment of osteomyelitis, with intraoperative findings corroborating the condition. There was a good clinical-radiological recovery associated with prolonged antibiotic therapy and satisfactory follow-up after hospital. PPT, which often results from an underdiagnosed or partially treated frontal sinusitis, is a condition that must be promptly recognized and directed to an adequate therapeutic approach due to the risk of serious complications that it entails.